Sources of antibiotics pollutants in the aquatic environment under SARS-CoV-2 pandemic situation - Sosa Hernández, Juan Eduardo; Rodas Zuluaga, Laura Isabel; López Pacheco, Itzel Y.; Melchor Martínez, Elda Madai; Aghalari, Zahra; Limón, Daniel Salas; Iqbal, Hafiz M.N.; Parra Saldívar, Roberto (2021)
During the last decades, the growth of concern towards different pollutants has been increasing due to population activities in large cities and the great need for food production by the agri-food industry. The effects observed in specific locations have shown the impact over the environment in air, soil and water. Specifically, the current pandemic of COVID-19 has brought into the picture the intensive use of different medical substances to treat the disease and population intensive misuse. In particular, the use of antibiotics has increased during the last 20 years with few regulations regarding their excessive use and the disposal of their residues from different sources. Within this review, an overview of sources of antibiotics to aquatic environments was done along with its impact to the environment and trophic chain, and negative effects of human health due prolonged exposure which endanger the environment, population health, water, and food sustainability. The revision indicates the differences between sources and its potential danger due toxicity, and accumulation that prevents water sustainability in the long run.